IDENTIFYING CAUSES OF MATHEMATICAL MISCONCEPTIONS AND PROPOSED STRATEGIES: A STUDY ON 4TH-GRADE STUDENTS USING TIMSS 2015 ITEMS - Sisi, Narjes Kargari (JME (Journal of Mathematics Education), 2025)
This study aimed to identify the primary causes of mathematicalmisconceptions (MMCs) among 4th-grade elementary school boys whensolving selected items from the Trends in International Mathematics andScience Study (TIMSS) 2015, and to propose appropriate strategies foraddressing them. The independent variable was the instructional interventionusing targeted strategies, while the dependent variable was the occurrence ofMMCs. The sample consisted of 40 male students from Shahid BeheshtiPublic Elementary School in Tehran, Iran, randomly assigned to anexperimental group (n = 20) and a control group (n = 20). After a pretest, theexperimental group received strategy-based instruction aimed at reducingMMCs, whereas the control group received no intervention. Both groupsthen completed a post-test. Data were analyzed using analysis of covariance(ANCOVA). The results showed that implementing targeted instructionalstrategies significantly reduced the frequency of MMCs. Six commonmisconceptions were identified, and corresponding strategies wereintroduced. These findings suggest that strategy-based instruction can be avaluable tool for promoting deeper conceptual understanding in mathematicseducation.